Family Quality as a Foundation for Adolescent Religiosity and Mental Health - Hartanto, Dody; Zakaria, Gamal Abdul Nasir; Fauziah, Mufied; Supriyanto, Supriyanto; Rizal, Yenni; Nugraha, Ariadi (Islamic Guidance and Counseling Journal, 2025)
Understanding the impact of family quality on adolescent religiosity and mental health is crucial for developing effective interventions and support systems, as family dynamics significantly influence religious beliefs and psychological well-being during formative years. This study investigates the influence of family quality on religiosity and mental health among high school and vocational school students in the cities of Yogyakarta and Pontianak, Indonesia, providing a representative sample of urban students with diverse backgrounds. The study employs purposive sampling techniques to select 1,795 students, with data collected using scales specifically developed to measure family quality, religiosity, and adolescent mental health. The construct validity of each item was tested using confirmatory factor analysis (CFA) within a structural equation modeling (SEM) framework, with a loading factor criterion of > 0.7 to indicate adequate validity in representing its respective construct. Reliability was assessed through Cronbach’s Alpha, yielding scores as follows: Family Quality at 0.863, Religiosity at 0.829, and Mental Health at 0.925. These values demonstrate that all three instruments exhibit a high level of reliability. Structural Equation Modeling (SEM) is utilized to analyze the data, accommodating complex dependent variables and inter-variable relationships. SEM analysis reveals significant positive relationships between family quality and both religiosity and mental health, highlighting the profound impact of family interactions on students' religious practices and psychological well-being. These findings emphasize the crucial role of family quality in enhancing religiosity and mental health among adolescents, suggesting that improving family dynamics could be a vital intervention strategy in educational and health domains.